O03.4 Genomic Epidemiology of Neisseria Gonorrhoeae with Reduced Susceptibility to Cefixime in the United States. (13th July 2013) - Grad, Y H; Kirkcaldy, R; Trees, D; Dordel, J; Goldstein, E; Weinstock, H; Parkhill, J; Hanage, W P; Bentley, S; Lipsitch, M
Abstract : Background: Genome sequencing of pathogens has yielded insights into transmission networks and the spread of antibiotic resistance. Here, we report a large-scale genomic epidemiology study of Neisseria gonorrhoeae to investigate the emergence and spread of isolates with reduced susceptibility to cephalosporins. Methods: We sequenced the genomes of 242 gonococcal isolates collected by CDC's Gonococcal Isolate Surveillance Program (GISP). These isolates comprise all 141 isolates from GISP in 2009–10 with reduced susceptibility to cefixime (cef RS ; cefixime MICs ≥ 0.25 µg/ml) and 141 susceptible isolates matched by location, collection date, and sexual orientation of the infected individual. We assessed diversity and association of genes known to contribute to antibiotic resistance, correlated location and phylogenetic clustering to determine sexual networks, and characterised the extent of recombination. Results: Phylogenetic analysis of single nucleotide polymorphisms (SNPs) within the core genome (34959 SNPs) demonstrates that most cef RS isolates in the US fall into two distinct lineages. We identify several independent acquisitions of a mosaic penA allele, including evidence of a partial mosaic in an isolate with cef RS and of reversion to an allele conferring cephalosporin susceptibility. Correlating the phylogeny with sexual orientation and geographic location provides evidence for clones circulating in sexual networks, some of which appear geographically restricted and others widespread. Analysis of predicted recombinant regions shows evidence of exchange with other Neisseria spp., consistent with prior observations of interspecies mosaicism. Conclusions: Cef RS isolates in the US predominantly derive from two lineages that share the same mosaic penA sequence, and reflect sexual networks at local and regional scales. Additionally, we quantify the extent of recombination and the correlation of selected alleles with resistance phenotypes. Genomic methods offer detailed insights into the spread of resistant infections, with potential for enhanced surveillance and improved diagnostics.